Variants in KLK11, affecting signal peptide cleavage of kallikrein-related peptidase 11, cause an autosomal-dominant cornification disorder. (20th October 2022) - Gong, Zhuoqing; Dai, Shangzhi; Jiang, Xingyuan; Lee, Mingyang; Zhu, Xuejun; Wang, Huijun; Lin, Zhimiao
Abstract: Background: Mendelian disorders of cornification (MeDOC) are a group of heterogeneous genodermatoses with different genetic bases. The pathogenesis of a substantial group of MeDOC remains to be elucidated. Objectives: To identify a new causative gene and the pathogenesis of a previously undescribed autosomal-dominant cornification disorder. Methods: Whole-exome sequencing was performed in three families with the novel cornification disorder to identify the disease-causing variants. As the variants were located around the signal peptide (SP) cleavage site of a kallikrein-related peptidase, SP cleavage, subcellular localization and extracellular secretion of the variants were evaluated in eukaryotic overexpression systems by Western blotting or immunocytochemistry. Then the trypsin-like and chymotrypsin-like proteolytic activity of the peptidase and degradation of its catalytic substrate were assayed using the patients' stratum corneum (SC) samples. The morphology of the lamellar bodies and corneodesmosomes (CDs) in the patients' SC was ultrastructurally examined. A mouse model harbouring the equivalent variant was constructed and evaluated histologically. Results: We identified two heterozygous variants affecting Gly50 in kallikrein-related peptidase (KLK)11 in a familial case and two sporadic cases with the new disorder, which is characterized by early-onset ichthyosiform erythroderma or erythrokeratoderma. KLK11 belongs to the family of kallikrein-related peptidases participating in skin desquamation by decomposing CDs, a process essential for shedding of the SC. In vitro experiments demonstrated that the variants perturbed the SP cleavage of KLK11, leading to subcellular mislocalization and impaired extracellular secretion of the KLK11 Gly50Glu variant. Both trypsin-like and chymotrypsin-like proteolytic activities were significantly decreased in the patients' SC samples. Reduced proteolysis of desmoglein 1 and delayed degeneration of CDs were detected in patients' SC, indicating delayed skin desquamation. Consistently, the patients showed a thickened, dense SC, indicating abnormal skin desquamation. Mice harbouring the homozygous c.131G>A (p.Gly44Glu) Klk11 variant, which is equivalent to KLK11 c.149G>A (p.Gly50Glu) in humans, exhibited hyperkeratosis and abnormal desquamation, partially recapitulating the phenotype. Conclusions: We provide evidence that variants at Gly50 affecting the SP cleavage of KLK11 cause a new autosomal-dominant cornification disorder with abnormal desquamation. Our findings highlight the essential role of KLKs in maintaining homeostasis of skin keratinization and desquamation. Abstract : Two different missense variants in KLK11 affecting Gly50 were identified in three unrelated cases with an autosomal-dominant cornification disorder characterized by abnormal skin desquamation. Complementary in vitro and in vivo analyses further confirmed the pathogenicity of these variants. This is the first monogenic human skin disorder caused by variants in KLKs gene. Our study highlights the essential role of KLK11 in the regulation of KLKs cascades during skin desquamation and paves a way for developing therapeutic options towards the disorders with skin barrier dysfunction.